Buku Ilustrasi 4 Macam Kepribadian Remaja 16-18 Tahun - Sarah Zhafirah; Masnuna Masnuna; Aditya Rahman Yani (Program Studi Desain Komunikasi Visual, Fakultas Sains dan Teknologi, Universitas Ma Chung, 2020)
Very few adolescents are aware of the importance of recognizing the concept of personal personality in Indonesia, even though this is one of the important thing teenagers must understand so that they can maximize their teenage years and arrange their way of life as early as possible. Most books on personality consist of boring text and difficult language for adolescents to understand and does not interest them. Many disadvantages from not understanding the concept of personality, including the creation of social reactions. Based on interviews and questionnaires, adolescents do not know their personalities and personality types so that they cannot recognize and maximize their potential. Overcoming this problem was finally designed an illustration book that aims to simplify the message of the importance of recognizing one's personality and understanding 4 types of personality. Illustration is communicative and make it easier for readers to understand messages through visuals